KEHARMONISAN KELUARGA DAN KENAKALAN REMAJA PADA SISWA KELAS 9 MTS NEGERI 2 PALEMBANG - Desy Oktaviani; Lukmawati Lukmawati (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2018)
The goal of this research is for examine relationship between harmony family with delinquency teenagers. The sample of this research is IX class of the MTs negeri 2 palembang consist of 173 Students. The methods used data using the Statistical Programme for Social Science (SPSS) versi 20.00 for windows to test the relationship between harmony of family and delinquency teenagers. The result of Product Moment Correlation showed the number r= -0,598 with ρ = 0.000 where (ρ<0.01), it can be concluded that there is a negative relationship which is significant between harmony family and deliquency teenagers from IX class students of MTs Negeri 2 Palembang. The Negative association shows that the higher that harmony family the lower is delinquency teenagers vice verse lower is harmony family the increasingly high deliquency teenagers happened.